The relationship between social capital and food security in farmer households (case study: Sedayulawas Village, Lamongan Regency – Indonesia) - Fauziah, Septia Hana; Prayitno, Gunawan; Dinanti, Dian; Hidayana, Izatul Ihsansi (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2023)
Sedayulawas Village is one of the villages contributed to the positive growth of Lamongan Regency in the fourth quarter of 2020. It has been named the selected pilot project for eradicating extreme poverty with the target of increasing community food security. However, this program was not supported by the relationship between farmers and farmer group leaders, as the trust of farmers to the group leaders were low since they couldnot protect farmers from many conflicts within the group. To ensure the success of programs of food security, the social capital of among farmers was an alternative mechanism for the community to increase food security. This study aimed to reveal how the contribution of the social capital of farmer households to food security in the Food Self-Sufficiency Program in Sedayulawas Village, Brondong District, Lamongan Regency. Descriptive statistical analysis to determine food security conditions were done using Confirmatory Factor Analysis (CFA) followed by Structural Equation Modeling (SEM). The result showed that there is a direct and indirect relationship between social capital and food security which has a significant value at the 5% test level. The food utilization variable explained 86.6% of farmers’ food security variability and the results of t-test showed that social capital has a significant effect in supporting the food security program for farmers in Sedayulawas Village.